Amoxicillin Plus Clavulanic Acid Versus Appendicectomy for Treatment of Acute Uncomplicated Appendicitis - Muhammad Shoaib Khan, Hakim Jan, Nadir Saifullah Khan, Ulas Khan, Saman Naz, Muhammad Farooq, (Pakistan Journal of Medical & Health Sciences, 2022)
Acute appendicitis is the most common indication for surgery in patients admitted to hospital for acute abdominal pain. In about 20% of cases, acute appendicitis is complicated, leading to local or diﬀuse peritonitis mostly. Although urgent appendicectomy is still the recommended treatment for acute uncomplicated appendicitis and also antibiotic treatment can cure acute appendicitis or can be the ﬁrst line of treatment. In the Current study we assessed the eﬃcacy of amoxicillin plus clavulanic acid by comparison with emergency appendicectomy for treatment of patients with uncomplicated acute appendicitis. In this Study open-label, non-inferiority, randomized trial, adult patients (aged 18–68 years) with uncomplicated acute appendicitis, as assessed by CT scan, were enrolled at Pakistan Instiute of Medical Sciences (PIMS) Hospital Islamabad Pakistan. A computer-generated randomization sequence was used to allocate patients randomly in a 1:1 ratio to receive amoxicillin plus clavulanic acid (3 g per day) for 8–15 days or emergency appendicectomy. The primary endpoint was occurrence of post intervention peritonitis within 30 days of treatment initiation. Non-inferiority was shown if the upper limit of the two-sided 95% CI for the diﬀerence in rates was lower than 10 percentage points. Both intention-to-treat and per-protocol analyses were done. The Current research Result show that Of 243 patients randomised, 123 were allocated to the antibiotic group and 120 to the appendicectomy group. Four were excluded from analysis because of early dropout before receiving the intervention, leaving 239 (antibiotic group, 120; appendicectomy group, 119) patients for intention-to-treat analysis. 30-day post intervention peritonitis was signiﬁcantly more frequent in the antibiotic group (8%, n=9) than in the appendicectomy group (2%, n=2; treatment diﬀerence 5·8; 95% CI 0·3–12·1). In the appendicectomy group, despite CT-scan assessment, 21 (18%) of 119 patients were unexpectedly identiﬁed at surgery to have complicated appendicitis with peritonitis. In the antibiotic group, 14 (12% [7·1–18·6]) of 120 underwent an appendicectomy during the ﬁrst 30 days and 30 (29% [21·4–38·9]) of 102 underwent appendicectomy between 1 month and 1 year, 26 of whom had acute appendicitis (recurrence rate 26%; 18·0–34·7).The Current result conclude that Amoxicillin plus clavulanic acid was not non-inferior to emergency appendicectomy for treatment of acute appendicitis. Identiﬁcation of predictive markers on CT scans might enable improved targeting of antibiotic treatment.